First Study of the Safety and Tolerability of Allvec-1, a Gene Therapy Vector, in Patients With Advanced Stage IV Malignant Solid Tumors - Jalali, Farzad; Moslemi, Dariush; Farjam, Arman (Reports of Radiotherapy and Oncology, 2015)
Background: Gene therapy relies on the delivery of foreign DNA into cells. More than 50% of all reported clinical trials for gene therapy are for cancer. Objectives: To test the tolerability, safety, and recommended phase II dose of Allvec-1, a highly selective gene therapy vector, after systemic administration in patients with advanced stage IV solid tumor malignancies. Patients and Methods: A phase I trial evaluated escalating doses of Allvec-1, administered 3 times weekly for 8 weeks in 6 patients with gastric, breast, esophageal, non-small cell lung cancer (NSCLC), and leiomyosarcoma. Clinical lab parameters, blood pressure, pulse and patients’ own-reported adverse events were used for evaluation of safety. The maximum dose was set based on the first sign of any minor side effect to be likely related to Allvec-1. Tumor imaging techniques were applied before and after Allvec-1 treatment for any tumor response. No further concomitant anti-tumor treatment was admitted during the study period. Results: Six patients [median age, 50.5 years (range, 23-66), they were heavily pretreated; received Allvec-1 starting at a dose of 1.25 × 1010 and increasing to the final dose of 2 × 1011 thrice weekly. During the study period 3 patients have received 24, one patient 21, one patient 14, and one patient 13 intravenous (I.V) injections, respectively. Treatment-related adverse events were nausea (1 out of 6) and increase of body temperature (38°C, 2 out of 6). These side effects were minor and lasted only up to 30 minutes, and disappeared after repeated dosing. The increase of body temperature occurred 24 to 48 hours after the treatments and was observed only during the second week. No other side effects were reported. All clinical lab and vital functions remained unaffected. An increase of body weight and an improvement of general condition could be observed in 4 out of 6 patients. One of these patients showed stable disease until the end of 4 weeks surveillance period. A partial response was seen in 1 out of 6 patients. Four patients died within one month after termination of the treatment due to the progressive dieses. Conclusions: Allvec-1, as the first gene therapy vector for systemic administration, was tolerated without any side effects. Dose-limiting toxicities were not observed in this study. Therefore, higher doses can be recommended in phase II trials. Despite extensive prior treatment and final stage of all patients a partial response and stable disease could be reached during the treatment period. It could be expected that a treatment beyond 8 weeks, even in those terminally ill patients, might increase the life expectancy without any side-effects. Therefore, additional clinical trials are well warranted in defining the role of Allvec-1 in treatment of cancer.